A Study of Retainability of Knowledge of BLS Taught in Foundation Course on Manikins after Six Months in First MBBS Students - Pradeep Kumar Shenoy C (International Journal of Health and Clinical Research, 2021)
Background: The cardiac arrest strikes anyone and a person with out-of-hospital cardiac arrest does not always be lucky enough to receive cardiopulmonary resuscitation. It may be due to a complete lack of competence of the common man in these situations. It is because of these observations made by authorities many health organisations in the world came up with the idea of training even the common man with BLS. So, National Medical Council also has laid down teaching guidelines for these fresher. National Medical Commission has done a superb job in mandating this but how far these skills will be learnt and how much will be retained is the million-dollar question. This study puts in a sincere effort to find the answers for this question. Aims and Objectives: To determine the retention of the BLS skill this has been taught after six months. Materials and Methods: One hundred fifty students will be undergoing the BLS course in the foundation course and immediately after the session a OSCE will be conducted so that the students will know the format of the examination and will be versed with the system and method of examination and the marks of the OSCE score will be noted in EXCEL format. After six months another OSCE session will be conducted which will serve as pre-test scores. The scores will be noted again in EXCEL sheet. The retention of the skill of BLS will be tested using the paired t test statistical analysis. Results: There was a significant difference between the OSCE scores initially when compared to the scores after six months. Conclusion: The training of the BLS should be started very early in the career of the budding students and reinforcement of the skill is needed.